PENGARUH JUMLAH UANG BEREDAR, SUKU BUNGA DAN NILAI TUKAR TERHADAP TINGKAT INFLASI DI INDONESIA MENGGUNAKAN PENDEKATAN ANALISIS JALUR PERIODE 2010Q1 – 2020Q4 - Herania, Elisabeth; Maski, Ghozali (Contemporary Studies in Economic, Finance and Banking, 2022)
Monetary policy is one of the important components in an economic system whose conditions are always uncertain. One of the most important objectives of monetary policy is to maintain price stability for goods and services. Price volatility, which is manifested as inflation, can have a bad long-term impact on the national economy if it is not controlled properly. Therefore, it is important to control inflation to maintain a healthy economic climate. A low and stable inflation rate is important for long-term economic growth. Monetary policy instruments that can maintain price stability include the money supply, interest rates and exchange rates. Therefore, this study aims to analyze the effect of JUB, interest rates and exchange rates on the inflation rate through path analysis method. Path analysis method is used to see the direct and indirect effect of the money supply on inflation through interest rates and exchange rates as intervening variables. The results showed that the money supply and exchange rate directly did not have a significant effect on the inflation rate. Meanwhile, interest rates have a significant direct effect on inflation. Indirectly, only interest rates have a role in mediating the relationship between the money supply and the inflation rate. Keywords: monetary policy; inflation; money supply; interest rate; exchange rate; path analysis